1999
DOI: 10.1007/s100510050819
|View full text |Cite
|
Sign up to set email alerts
|

Can one hear the shape of an electrode? I. Numerical study of the active zone in Laplacian transfer

Abstract: The concept of active zone in the Laplacian transport to and across irregular interfaces is rigorously introduced. It applies to arbitrary geometries and uses the coarse-graining method proposed by Sapoval to compute the flux across an irregular interface from its geometry without solving the general Laplace problem. Such transport play a dominant role in electrochemistry, heterogeneous catalysis and physiological diffusion processes. In the field of electrochemistry, the method permits one to predict the impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 20 publications
2
49
0
Order By: Relevance
“…In the work described in the preceding paper [1], a first answer to this question has been given. By transforming it in a purely mathematical problem named "problem I".…”
Section: Introductionmentioning
confidence: 96%
“…In the work described in the preceding paper [1], a first answer to this question has been given. By transforming it in a purely mathematical problem named "problem I".…”
Section: Introductionmentioning
confidence: 96%
“…Then, in physical terms, ⌳ corresponds to the maximal perimeter length of a planar cut of the exchange surface on which screening effects can be neglected, hence its designation as ''unscreened perimeter length.'' The role of ⌳ as ''unscreened perimeter length'' has been thoroughly studied in D ϭ 2, theoretically, numerically, and experimentally (6,(9)(10)(11).…”
mentioning
confidence: 99%
“…More recently, they showed that the frequential behavior of a rough electrode could be obtained by studying the spectral properties of the so-called self-transport operator [5,6]. The latter measures the probability for two given sites of an interface to be linked by random walk through the electrolyte.…”
Section: Introductionmentioning
confidence: 99%